Low CD4 count was characterized in recent HIV CRF01_AE infection and it rapidly increased to reach a peak in the first year since ART initiation - Xue-Ying Zhang; Li Wang; Yue Jiang; Si-Miao Huang; Hong-Rui Zhu; Wei Liu; Jia-Ye Wang; Xiang-Hui WEI; Yi-Lin Zhao; Wen-Juan Wei; Teng Fei; Xiao-Hong Chen; et al. (BMC Infectious Diseases)
Abstract Background Currently, most people living with HIV (PLWH) in China have a strong awareness of diagnosis and treatment in the early stage of HIV infection. Subtype-specific virological and immunological features of recently infected PLWH have not yet been elucidated. Methods Data including CD4 count and viral load (VL) of 1508 anti-retroviral therapy (ART) -naïve PLWH were obtained from the HIV Database and comparatively analyzed among PLWH with different HIV subtypes. The infection status of 402 newly diagnosed and ART-naïve PLWH from a cohort of men who have sex with men (MSM) in China was evaluated using diagnosis records and LAg-Avidity EIA. Based on partial pol genes, HIV genotypes in 120 recent, 68 long-term, and 54 chronic infections were identified. The CD4 count, CD8 count, and VL, as well as trajectories of dynamic CD4 counts during ART of local PLWH with different HIV subtypes, were compared using non-parametric tests. Results For the HIV database, the CD4 count in PLWH with CRF01_AE was lower than that in PLWH with CRF07_BC or subtype B. For the recently infected local PLWH, CRF01_AE was the dominant HIV subtype (65.83%), followed by CRF07_BC (18.33%) and subtype B (15.83%). Recent CRF01_AE infections showed a lower baseline CD4 count than CRF07_BC infections. During ART for recently infected PLWH, the CD4 count in the CRF01_AE group rapidly increased to reach a peak at the end of the first year post-ART, while the CD4 count in the CRF07_BC group increased slowly to reach a plateau at the end of the third year. The CD4 count in the subtype B group increased significantly to reach a plateau within the first two years and then its trajectory overlapped with that of the CRF07_BC group at the end of the third year post-ART. Conclusions CRF01_AE rapidly reduced CD4 count during the recent HIV infection. The CD4 count of the recently infected individuals with CRF01_AE increased sharply and reached its highest level of recovery within the first year of ART initiation. This study revealed an important time point for estimating CD4 count recovery post-ART in individuals with different HIV subtypes.